Entrepreneurial Capability and Digital Literacy as Drivers of Micro-Enterprise Sustainability in Surabaya, Indonesia - La Himmah il Princess Choris (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
Micro-enterprises increasingly depend on internal managerial capabilities and effective engagement with digital technologies to maintain sustainable performance under changing market conditions. This study examines the relationships between entrepreneurial capability, digital literacy, and micro-enterprise sustainability in Surabaya, Indonesia, while comparing the relative contribution of the two predictors. A cross-sectional quantitative survey was conducted involving 55 micro-entrepreneurs selected through purposive sampling. Entrepreneurial capability, digital literacy, and sustainability were measured using a five-point Likert scale, and the data were analysed through partial least squares structural equation modelling. The findings show that entrepreneurial capability is positively and significantly associated with micro-enterprise sustainability, with a path coefficient of 0.588, a test statistic of 5.398, and a probability value below 0.001. Digital literacy also demonstrates a positive and significant relationship with sustainability, with a path coefficient of 0.279, a test statistic of 2.599, and a probability value of 0.009. Entrepreneurial capability therefore exhibits a stronger relationship with sustainability than digital literacy. Active learning, analytical ability, passion, and self-achievement emerged as prominent elements of entrepreneurial capability, while information management and digital safety were central components of digital literacy. These results indicate that digital competence is valuable but may generate greater sustainability benefits when supported by leadership, managerial judgement, and the ability to translate technological resources into business decisions. The study contributes contextual evidence from an Indonesian urban setting by integrating entrepreneurial capability and digital literacy within one model of economic, social, and environmental sustainability. Capacity-development initiatives should therefore combine entrepreneurial training with practical digital-literacy and cybersecurity education.